Commodification, Spatialization, and Structuring in Instagram (Vincent Mosco's Descriptive Political Economy Study on Instagram Anies Baswedan Related to Covid-19) - Rifka Hanifah; Vinda Fauzia Hamdani Putri; Ajeng Setia Utari (Universitas Djuanda Bogor, 2021)
Instagram is one of the social media that is widely used by Indonesians. Instagram users in Indonesia are under Instagram users from the United States, Brazil and China. The emergence of social media Instagram is a new and interesting dynamic to research based on Vincent Mosco's descriptive study of the political economy of the economy. One way to see and analyze an issue or phenomenon of communication is through the descriptive study of Vincent Mosco's political economy and economy. In theory, Mosco refers to the globalization of the political economy of media which explains where there is a transition from old media and when new media emerge. Thus the formulation of the problem of this research is how the political economy practice of communication in the use of Instagram social media during the Covid-19 pandemic which was observed from Anies Baswedan's Instagram account. This study uses a descriptive research method in order to provide an overview description of the political economy practice of communication on Instagram social media during the Covid-19 pandemic which was observed from the Instagram account of the Governor of DKI Jakarta, Anies Baswedan. It can be concluded that social media is a means based on internet technology (online media) such as Instagram which allows a person to interact, communicate, collaborate and share information with others. Even Instagram users can easily participate directly in it. Commodification, spatialization and structuration are three important elements in political economy because they can bring about changes in function or use values. Commodification is one of the elements that is directly related to how the process of transforming goods or services (along with their use value) into a commodity that has an exchange value in the market. Spatialization is a process when dealing with time and space. Structuring is a communication or media activity associated with social structures.